PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT. CHAROEN POKPHAND TBK - Akhmad Akbar; Eka Rahim; Endang Nurita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the company's profitability ratio, one of the measuring tools is Return On Assets (ROA), with the liquidity ratio and solvency ratio factors. The liquidity ratio is the Current Ratio (CR) and the solvency ratio is the Debt to Equity Ratio (DER). Apart from that, this research also examines the role of Return On Assets on the Current Ratio and Debt to Equity Ratio. The research was conducted within the scope of the company PT. Charoen Pokphand Indonesia Tbk. The method used is Quantitative by carrying out a quantitative Descriptive Analysis test, Classical Assumption Test consisting of Normality Test, Heteroscedasticity Test, Multicollinearity Test, Autocorrelation Test which is continued with Simple and Multiple Linear Regression Tests then Hyopothesis Tests namely T Test and F Test and finally Test the Coefficient of Determination using the SPSS software tool. The research years used were 12, namely from 2011 to 2022. The results of this research were both simultaneous and partial between variables, there was no significant CR variable, and DER on ROA at PT. Charoen Pokphand Indonesia Tbk.